Controlled flow over a finite square cylinder using suction and blowing. (June 2019) - Rastan, M.R.; Sohankar, A.; Doolan, Con; Moreau, Danielle; Shirani, E.; Alam, Md. Mahbub
Highlights: Three-dimensional flow around a finite wall square cylinder is simulated at Re of 250. Extensive analysis is done of forces, vortex shedding frequency, and wake structures. Both blowing and suction have the potential to reduce forces. Suction strategy considerably affects the shedding type and wake flow topology. Abstract: Three-dimensional unsteady flow around a finite wall mounted square cylinder subjected to a steady secondary flow (blowing and suction) from the cylinder's front face has been studied with the aid of direct numerical simulations. The aspect ratio ( AR ) of the cylinder was varied as AR  = 2, 4 and 7 while the ratio Г of the secondary flow to the freestream velocity was changed as −4 ≤  Г  ≤ 4. All simulations were carried out at a Reynolds number ( Re ) of 250, based on the cylinder width, to investigate the influence of Г and AR on cylinder forces, vortex shedding frequency, and mean and instantaneous wake structures. The results show that, independent of AR, both blowing and suction have the potential to reduce the time-mean forces (e.g. more than 90% pressure drag reduction), fluctuating forces and vortex shedding frequency. Furthermore, a detailed investigation of vortex evolution reveals that the suction strategy considerably affects the shedding type and wake flow topology. Increasing the suction ratio changes the shedding from symmetric to asymmetric at AR  = 4. Conversely, a planar jet attenuates vortical structures in the vicinity of the wall. Jet deflection is observed at Г  = 2 and 4, which plays a key role in the success of the control approach and in the determination of the wake flow structure by changing the pressure distribution on the front face. The effect of AR on the shedding of large-scale vortical structures is also examined. Two critical AR values are determined where the flow and the mean wake structure changed from steady to unsteady (2 <  AR  < 3) and from dipole to quadrupole ( AR  = 4), respectively. Graphical abstract: Image, graphical abstract